Co-assembly of foxtail millet prolamin-lecithin/alginate sodium in citric acid–potassium phosphate buffer for delivery of quercetin. (1st July 2022) - Chen, Xiao; Wu, Yan-Chao; Gong, Pi-Xian; Li, Hui-Jing
Highlights: Constant pH condition contributed to produce smaller prolamin particles. Novel hybrid nanoparticles formed by prolamin, lecithin, and alginate were fabricated. Electrostatic interactions and hydrogen bonds are the main driven forces. The composite NPs could enter epithelial cells in a time dependent manner. Cryoprotectants such as sucrose could re-disperse the prolamin nanoparticles. Abstract: Foxtail millet nanoparticles with smaller mean size at ∼130 nm and narrower polydispersity index at ∼0.05 were prepared in citric acid–potassium phosphate buffer (pH 8.0). Through lecithin (Lec)/sodium alginate (Alg) coating, a hydrophobic FP core, a Lec monolayer, and a hydrophilic Alg shell were formed spontaneously. Dissociation experiment revealed that electrostatic interaction and hydrogen bonding were main driving forces for the formation and maintenance of stable FP–Lec/Alg NPs. In addition, Lec/Alg coated NPs exerted an important role in sustaining the controlled release of the encapsulated quercetin under simulated gastrointestinal tract conditions. Cellular uptake test exhibited that FP-Lec-Alg NPs cold enter epithelial cells in a time-dependent manner, showing the maximum uptake efficiency were 22% and 24%, respectively, after 2 h of incubation. About 220 nm NPs can be recovered by adding 10% (w/v) sucrose. FP-Lec-Alg NPs were found to be promising delivery materials to deliver quercetin and improve its bioavailability.